Data analysis and mining of solar radiation - Loh, Jun Wei. (2009)
This project seeks to study the solar radiation readings particularly at Nanyang University (NTU) so that a forecast can be done to the solar radiation readings. The dataset is retrieved from a weather database which follows The National Weather Sensor Grid architecture that has been set under the National Weather Study Project (NWSP) to store data of all the weather stations in schools around Singapore. The solar radiation data will be smoothed and forecasted using mathematical calculations that are used for statistical forecast.